Evaluasi dan Pemilihan Desain Alternatif Instalasi Pengolahan Limbah Cair Industri Tahu-Tempe - Sona Putri Siswoyo; Ismi Khairunnissa Ariani; Basransyah; Bayu Nur Abdallah; Eka Masrifatus Anifah (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
The processing of tofu and tempeh produces solid waste and wastewater. Tofu and tempeh wastewater with high organic content must be treated to prevent environmental pollution. Therefore, the tempeh and tofu industry centre in East Kalimantan developed a wastewater treatment plant (WWTP) to treat the wastewater.However, the quality of the effluent still did not meet wastewater quality standards. In addition, the production of tofu and tempeh is increasing every year, so the amount of wastewater is also increasing. This study aims to evaluate and select alternative WWTP designs for tofu and tempeh wastewater. The WWTP design uses an anaerobic digester for wastewater treatment and combines it with three alternative aerobic treatments, including aerobic treatment, wetland and aerated lagoon. The design selection is based on removal efficiency, land area, and operating and construction costs using the Analytical Hierarchy Process method. Based on AHP, the selected design was the WWTP of the second alternative with wetlands. The selected design had a bar screen, an equalisation tank, an anaerobic digester and a wetland. This selected design had a BOD removal efficiency of 96%, COD of 92%, TSS of 88% and a land area of 12,524.20 m2 with a construction cost of IDR 4,330,301,632 and an operating cost of IDR 179,664,945.